Pemikiran tentang konstruksi sosial perpustakaan sekolah oleh Kepala Sekolah Menengah Atas di Surabaya - Imroatul Mufidah; Abdun Nashir (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2021)
A phenomenon of the establishment of libraries in Indonesia which is often motivated by practical and instrumental considerations, including at the level of high school libraries (SMA) in Surabaya, makes the research aimed at knowing the social construction of libraries for high school principals in Surabaya, and knowing the types of the type formed by the principal of a high school in constructing a school library in Surabaya. The research uses the theory of Peter L Berger and Thomas Luckmann, which involves the processes of Externalization, Objectivation, and Internalization. This research is a qualitative research with an interpretive approach. Determination of informants using a purposive method. The researcher reduced the informants so that they got 10 people. Data collection is done by direct observation (observation) and conducting in-depth interviews (in-depth interviews). From the results of this study obtained three typologies, the first is empathy leaders. This type considers the type of school and other infrastructure as equally important. Sympathy leaders consider the library important, with all its shortcomings, and are apathetic leaders. While the library is important, the school's main priority is more on infrastructure other than the library, such as a computer lab.